2013
DOI: 10.1111/mve.12043
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal abundance of livestock‐associatedCulicoidesspecies in northeasternBrazil

Abstract: Culicoides biting midges (Diptera: Ceratopogonidae) are of great medical and veterinary importance because the haematophagous females of some species can transmit diseases to humans and animals. In order to determine the presence and seasonal abundance of the bluetongue virus (BTV) vector Culicoides insignis Lutz at domestic animal sheds in northeastern Brazil, insects were collected once a month between January and December 2010. Light traps were set from 18.00 to 06.00 hours at a pigsty, chicken coop and bov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 12 publications
(14 reference statements)
0
15
0
1
Order By: Relevance
“…Other common species collected such as C. insignis and C. pusillus, are known to be major and potential vectors of BTV, respectively [9,44]. Culicoides insignis is a widespread species often associated with animals and commonly found in pasture environments with cattle and pigs [42,[45][46][47][48] and to a lesser extent attracted towards poultry [41]. In spite of the low numbers collected, the roles of C. paraensis involved in OROV and C. debilipalpis, another competent BTV vector [49], should be considered in future health surveillance programs both for their vectorial capacity and annoyance of humans [50].…”
Section: Discussionmentioning
confidence: 99%
“…Other common species collected such as C. insignis and C. pusillus, are known to be major and potential vectors of BTV, respectively [9,44]. Culicoides insignis is a widespread species often associated with animals and commonly found in pasture environments with cattle and pigs [42,[45][46][47][48] and to a lesser extent attracted towards poultry [41]. In spite of the low numbers collected, the roles of C. paraensis involved in OROV and C. debilipalpis, another competent BTV vector [49], should be considered in future health surveillance programs both for their vectorial capacity and annoyance of humans [50].…”
Section: Discussionmentioning
confidence: 99%
“…De acordo com Andrade et al (2008) essa microrregião possui temperaturas médias anuais em torno dos 20°C, podendo passar dos 30°C nas épocas mais quentes e 15°C no período mais frio, com chuvas principalmente de abril a agosto (Borges Júnior et al 2012). Esses eventos podem contribuir para o aumento da população de insetos pelo aumento do desenvolvimento larval proporcionado pelas condições ambientais da região (Carvalho & Silva 2014).…”
Section: Discussionunclassified
“…Greater numbers of this species were collected when light and cattle traps were used for attraction on cattle farms in the American Virgin Islands and in the Caribbean Region, respectively (Greiner et al , ; Saenz & Greiner, ). Of three outdoor environments in the northeast of Brazil, Carvalho & Silva () found that 98.2% of C. insignis were collected in cattle corrals. In southern Florida, 99.9% of C. insignis were captured in light traps (Kramer et al , ).…”
Section: Culicoides Captured In Pasture and Forest Environments In Rumentioning
confidence: 99%